2011
DOI: 10.1007/s00580-011-1265-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary enzyme on some blood biochemical parameters of the cultured great sturgeon Huso huso juveniles

Abstract: In this study the effects of dietary exogenous enzyme (Kemin®; 0, 250, 500, 750 and 1,000 mg/kg) on certain blood biochemical parameters (total protein, glucose, cholesterol) and serum magnesium in cultured great sturgeon (Huso huso) juveniles were determined. Juveniles (mean weight 10.2±0.8 g) were fed three times a day at 5-10% body weight for 46 days. Serum total protein concentration remained unaffected except in fish fed with 750 mg/kg enzyme which was significantly higher than the other treatments. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The expansion of global aquaculture is increasing the demand for aquaculture feed, which is the prime input in fish culture practices (Singh et al, 2011). The supplied diet must contain the necessary nutritional requirements for the fish to ensure the best growth (Ghomi et al, 2012). World aquaculture is the fastest growing food-producing sector in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of global aquaculture is increasing the demand for aquaculture feed, which is the prime input in fish culture practices (Singh et al, 2011). The supplied diet must contain the necessary nutritional requirements for the fish to ensure the best growth (Ghomi et al, 2012). World aquaculture is the fastest growing food-producing sector in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The beluga (Huso huso) and the sevruga (Acipenser stellatus) are of the most important species of sturgeon sh (Acipenseridae) inhabited in the Caspian Sea in the north of Iran with a high demand for products such as caviar, meat, skin, and cartilage (Ghomi et al 2012; Asgari et al 2013;Hashemi et al 2018). Today, the sturgeons are considered as the vulnerable sh species for different reasons like over shing for production of meat and caviar, water pollution and destruction of their natural habitat (Babaei et al 2011;Ghasemi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes reduce the quality and quantity of available substrate for microbes, decrease the viscosity of intestinal contents and increase the rate of substance transmission by increasing the rate of digestion and production of simple sugars from diet fibre, thus reducing the harmful microbial population of the intestine. Enzymes also reduce fermentation in the intestine and increase fermentation in the cecum by increasing the digestibility of dietary nutrients (Ghomi et al., 2012; Sun & Kim, 2019). Some substances digested by gastrointestinal enzymes may not be absorbed in the small intestine and be transferred to the cecum, thus increasing bacterial fermentation in the cecum (Ghomi et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes also reduce fermentation in the intestine and increase fermentation in the cecum by increasing the digestibility of dietary nutrients (Ghomi et al., 2012; Sun & Kim, 2019). Some substances digested by gastrointestinal enzymes may not be absorbed in the small intestine and be transferred to the cecum, thus increasing bacterial fermentation in the cecum (Ghomi et al., 2012). It has been reported that enzyme supplements can increase the growth performance of poultry by up to 10% (Daghigh Kia et al., 2017).…”
Section: Introductionmentioning
confidence: 99%